In vitro effects of chlorpyrifos on gonadotropin-induced oocyte maturation and steroidal interplay of freshwater catfish, heteropneustes fossilis - A. MISHRA; S. VERMA (International Journal of Pharma and Bio Sciences, 2017)
In vitro effects of chlorpyrifos (CPF) on hCG-induced oocyte maturation (OM) were investigated in Heteropneustes fossilis. The interplay of different steroids that involve in oocyte maturation was also explored. Incubations of post-vitellogenic follicles with human chorionic gonadotropin (hCG) alone induced OM in a concentration and duration-dependent manner. However, CPF showed inhibitory effects on hCG induced GVBD in co-incubation experiments. Effective dose of hCG (1.7 mg/ml, 8 hr) induced OM coincided with a significant increase in follicular pregnenolone, progesterone, deoxycorticosterone (DOC) and dihydroxyprogesterone (DHP) and decrease in estradiol-17β (E2) as compared to control group follicles. Under, CPF exposure, follicles elicited a significant sharp decrease in pregnenolone, progesterone and DHP. However, DOC and E2 increased significantly. Co-incubation study revealed that CPF suppressed hCG induced concentrations of DHP, pregnenolone and progesterone significantly but side by side support DOC increase and maintain high estradiol-17β. Thus, the present results suggested that the CPF inhibited hCG induced oocyte meiotic maturation due to suppression of C21 steroids within the follicle.